The role of ceramide, menthol, and polidocanol on pruritus, skin barrier function, and disease severity of mild atopic dermatitis - Umborowati, Menul Ayu; Nurasrifah, Dewi; Indramaya, Diah Mira; Anggraeni, Sylvia; Damayanti, Damayanti; Prakoeswa, Cita Rosita Sigit (Journal of Pakistan Association of Dermatologists, 2020)
Background Atopic Dermatitis (AD) relates with skin barrier defect. Unbearable itch leads to intense scratching, causing skin damage, and perpetuates the disease. The aim of this study is to investigate efficacy of topical ceramide, menthol, and polidocanol to decrease itch and AD severity, also improve skin barrier function. Methods Total 30 subjects were included in this pre-experimental, before-after observational study. The subjects were children 8-18 years old with mild atopic dermatitis. We evaluated SCORAD index and daily patient-based Patient Eczema Scoring Time (PEST) for AD severity, transepidermal water loss (TEWL) using Tewameter to represent skin barrier function, and also visual analog scale (VAS) to observe itch. The preparation was applied twice daily for 4 weeks. The progression of AD after application, along with side effects, was evaluated on 5 minutes, week 1, 2, and 4. Results SCORAD index started to decrease after 1-week application. PEST and itch VAS decreased as immediate as 5 minutes after application. Skin barrier function also improved represented by declining of TEWL values. The differences were statistically significant (P < 0.05). Conclusion Combination of ceramide, menthol, and polidocanol suppress itchy and disease severity, also improve skin barrier function in AD patients.